Healthcare professionals’ opinions regarding health coaching for patients with diabetes: A pilot exploration in Indonesia - Niken Safitri Dyan Kusumaningrum; Fatikhu Yatuni Asmara; Devi Nurmalia (Belitung Nursing Journal, 2022)
Background: Diabetes management is applied for the entire patients’ lives, so it requires lifelong sustainable self-management actions to have a positive impact. Integrated care as coaching intervention is considered a program that facilitates and supports patients in managing diabetes more effectively and optimally. However, there are limited studies regarding this program in Indonesia. Objective: This study aimed to explore the opinions of healthcare professionals concerning the importance of health coaching for patients with diabetes in Indonesia. Methods: An invitation letter via email was distributed individually to participants from the three provinces of Java, Indonesia, between June and August 2020. The open-ended questions that consist of two sections were developed to explore the matter related to health coaching for patients with diabetes. A descriptive analysis of the participants’ answers was used to explain the data comprehensively and accurately reveal the complete information. Results: A total of seven healthcare professionals from four professions participated in the study. Based on healthcare professionals’ opinions, this study revealed that the most common reason health coaching needs to be implemented is related to self-management in dealing with diabetes. Health coaching as a tailored-intervention strategy in diabetes self-management requires a multidisciplinary approach and considers the local wisdom to achieve the expected goals in all aspects of patients’ lives. Thus, health coaching as an integral part of diabetes self-management is considered an appropriate program to cope with this problem. Conclusion: Health coaching for patients with diabetes is useful and reasonable to implement among patients with appropriate strategies, especially in Indonesia and beyond.